Kaposi’s Sarcoma-Associated Herpesvirus microRNAs - Gottwein, Eva (Frontiers in Microbiology, 2012)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is a human pathogenic γ-herpesvirus strongly associated with the development of Kaposi’s Sarcoma and B cell proliferative disorders, including primary effusion lymphoma (PEL). The identification and functional investigation of non-coding RNAs expressed by KSHV is a topic with rapidly emerging importance. KSHV miRNAs derived from 12 stem-loops located in the major latency locus have been the focus of particular attention. Recent studies describing the transcriptome-wide identification of mRNA targets of the KSHV miRNAs suggest that these miRNAs have evolved a highly complex network of interactions with the cellular and viral transcriptomes. Relatively few KSHV miRNA targets, however, have been characterized at a functional level. Here, our current understanding of KSHV miRNA expression, targets, and function will be reviewed.